Advances in cancer research. - Vande Woude, George F.; Klein, George, 1925-2016 (Advances in cancer research, 2000)
Advances in Cancer Research provides invaluable information on the exciting and fast-moving field of cancer research. Here once again, outstanding and original reviews are presented. Key Features * New Paradigms for the Treatment of Cancer: The Role of Anti-aiogenesis Agents * The Hepatocyte Growth Factor/Met Pathway in Development, Tumorigenesis, and B-Cell Differentiation * Clinical Targets for Anti-metastasis Therapy * Animal Models of Melanoma: Recent Advances and Future Prospects * The Indispensable Role of Microenvironment in the Natural History of Low-Grade B-Cell Neoplasms * Epstein-Barr Virus Latency: LMP2, a Regulator or Means for Epstein-Barr Birus * Biochemistry and Pathological Importance of Mucin-Associated Antigens in Gastrointenstinal Neoplasia * Studies on Polyomavirus Persistence and Polyomavirus-Induced Tumor Development in Relation to the Immune System.